Knowledge, Attitude, and Perception Towards Condom Use among Female Sex Workers in North Jakarta: A Mixed-Method Study - Harzif, Achmad Kemal; Surya, Raymond; Chiprion, Ariel Timy; Mutia, Heidi Dewi; Puspawardani, Aisyah Retno; Ummah, Nafi'atul; Nurbaeti, Putri; Sayogo, Atikah; Wiweko, Budi (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2025)
Background: HIV/AIDS is a significant global health and social issue, particularly affecting sex workers, who are the second most common high-risk population. Efforts have been attempted to address the challenges, including promoting safer sex and increasing sex workers’ awareness of condom use to reduce sexually transmitted disease (STDs) transmission. Objectives: This study aimed to examine the knowledge, attitude, and perception among FSWs in North Jakarta towards condom use to prevent HIV. Method: Using a validated WHO questionnaire, this cross-sectional community-based study was conducted in pubs and lounges in North Jakarta among 182 FSWs. The questionnaire was translated forward and backward to ensure accuracy. The data were analyzed using SPSS Statistics for Windows and transcription in MS Word for qualitative data. Results: The reliability test for knowledge and attitude were 0.427 and 0.456, respectively. The study found that most participants (75%) had good knowledge about the benefits of condom use, and most agreed that condoms are suitable for casual or established relationships. However, due to cultural barriers in Indonesia, most subjects (68.1%) felt embarrassed about buying condoms.  Conclusion: The study found that FSWs possess a good knowledge and attitude regarding the utilization of condoms to avert STDs, particularly HIV/AIDS. Nonetheless, there is a need to enhance FSWs’ attitudes towards condom use and perceptions of health services, particularly those related to STDs, given their classification as a population at high risk.